Profit Shifting, Employee Pay, and Inequalities: Evidence from US-Listed Companies - Baptiste Souillard (Center for Economic Studies and ifo Institute (CESifo), 2022)
Corporate tax avoidance has regularly been accused of aggravating income inequalities. Yet, systematic evidence on this matter is still lacking. To fill this gap, the present paper explores the effect of profit shifting on employee pay among S&P 1500 companies. The study shows that its effect indeed varies across occupations. Chief executive officers and chief financial officers receive higher compensations when their firm starts operating in tax havens. Non-executive employees, if anything, see their wages fall in the meantime. Furthermore, the inequality-deepening impact of firm entry into tax havens is driven by companies that reward executives on an after-tax basis and more pronounced in intangible-intensive companies. These new findings enrich our understanding of the distributional consequences of profit shifting. They also cast light on the evolution of income inequalities, public opinion about globalization, and ongoing debates on international tax reforms.
Keywords: F16; H26; J30; M12; 330; employee pay; multinational enterprises; profit shifting; tax havens; income inequalities